STYLISTIC ANALYSIS OF CLASSICAL AND MODERN LITERARY WORKS IN A LITERARY WORK - Irenne Edelwis Rondonuwu; Chika Laras Pramestuti; Putri Angel Lestari; Ichsan Fauzi Rachman (Media Inovasi Pendidikan dan Publikasi, 2023)
This research examines the differences in language style in two Indonesian literary novels, namely